PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN WISATAWAN BERKUNJUNG PADA FORT ROTTERDAM DI KOTA MAKASSAR - Nasrullah, Nasrullah; Hardianti, Hardianti (Institut Agama Hindu Negeri Gde Puda Mataram, 2023)
This research aimed to know the influence of Promotion Mix to the decision of tourists visiting Fort Rotterdam in Makassar City. The variables of this study are: (1) tourist visiting decisions as the dependent variable (Y) as measured by (2) advertising, and (3) publicity as the independent variable (X). The population of this research were visitors to Fort Rotterdam, with an accidentally sample of 130 respondents. Data was collected using a questionnaire. The data were analyzed using descriptive and inferential analysis. The equation of multiple linear regression in the analysis is Y= 2.841 + 0.170X1 + 0.316X2 + e. The results showed that variables; advertising and publicity partially had a significant influence on tourist visiting decisions. Furthermore, the variables; advertising and publicity had a significant influence simultaneously on the decision of tourists visiting Fort Rotterdam in Makassar City. The influence value of variable can be seen from the Determination Coefficient (R2) = 0.535. This research recommends that each promotional mix influence be used optimally to complement the promotion strategy in order to reach the target of increasing Fort Rotterdam number of tourist visits.